Karakteristik kualitas air dan pengaruhnya pada pertumbuhan benih ikan nila jatimbulan Tilapia (Oreochromis sp) di IPB Kepanjen, Malang - Pelu, Anselmus Mau; Liubana, Debora Victoria (Universitas Batangahari Jambi, 2025)
Water quality is a key factor that influences the success of Jatimbulan tilapia (Oreochromis sp) hatchery. Water quality parameters such as temperature, pH and dissolved oxygen must be maintained in optimal conditions to support the growth, reproduction and survival of seeds. Jatimbulan tilapia (Oreochromis sp) is one of the superior strains of tilapia which has the advantage of growing faster than other strains. The sustainability of the cultivation business, especially at the tilapia rearing stage, is very dependent on a stable seed supply and good water quality management, because water quality has a direct influence on the results of fish cultivation.This research aims to estimate the carrying capacity and production potential of Jatimbulan tilapia in the context of developing fisheries using traditional methods, by evaluating water quality aspects, namely physical and chemical factors. Sampling was carried out directly (in situ) in the spawning pond, with parameters measured including temperature, brightness, pH and dissolved oxygen (DO). Spawning is carried out to preserve the jatimbulan fish (Oreochromis sp) as well as produce superior seeds. Seed rearing shows a survival rate of up to 100%, a daily specific growth rate of 1.84 ± 0.06%/day. This shows that the quality of the waters at the Kepanjen Aquaculture Installation plays an important role in supporting successful spawning and producing superior quality aquaculture products.